Vocational Education Transformation Toward Maturity and Business Motivation - Hefni Hefni (Jurnal Ilmu Sosial Mamangan, 2019)
Indonesia must be ready to face the Asia Pacific 2020 free market. One thing that the authors focus on in this paper is that creative, dynamic and ready to compete human resources, reform and transformation and development in the field of vocational education (vocational) is wrong one author's opinion in this paper. Vocational education (vocational) is one of the solutions to improving Indonesia's Human Resources, because vocational education creates people who are ready to work in the field of work that is available on the field nationally and internationally and has the ability to open new jobs. The embodiment of creative human resources is the responsibility of education, especially vocational education, especially in preparing students to become subjects whose role is to showcase their strong, creative, independent, and professional excellence in their respective fields. This is because education is a process of humanizing humanity in the sense of actualizing all of its potentials into abilities that can be utilized in their daily lives in the wider community. One aspect that must be improved in vocational education is the management of education including teaching staff, in addition to facilities and infrastructure. This is very important to do with the aim that students have a vocational maturity and foster mental development or entrepreneurship motivation. Vocational education not only instills concepts, but rather focuses on understanding and work processes, therefore, for the advancement of vocational education, the potential of teaching staff and the completeness of facilities and infrastructure must be the main factors that must be reformed.